Early Children Care and Development Education (ECCDE) Administration in Nigeria: Challenges and Way Forward - Olowonefa, Grace Simadi (Researchparks Publishing, 2022)
This paper examined the challenges militating against effective administration of Early Children Care and Development Education (ECCDE) centres in Nigeria. Content analysis was adopted for the paper. Content analysis was adopted for the paper. Both secondary and primary data were sourced from national and international dailies, published, unpublished information resources to support points raised. The paper revealed that poor funding, shortage of professional care-giver, inadequate infrastructural facilities, corruption, insecurity, shortage of instructional materials, political instability, lack of current data, shortage of national curriculum and unstable educational policies are the challenges militating against effective administration of Early Children Care and Development Education (ECCDE) centres in Nigeria. It was recommended that the federal government should increase the percentage of funds allocated to the administration of early child education programme in the counterpart funding scheme. The state and local government should also increase the funding of the Early Children Care and Development Education (ECCDE) programme in Nigeria.